Compassionate accountability how leaders build connection and get results - Regier, Nate. (Oakland Berrett-Koehler Publishers, 2023)
"This book is a compass for leaders lost in the paradoxical space between being compassionate and holding people accountable. Compassion and accountability have generally been considered at odds with each other in the management space. Solely prioritizing accountability can create toxic work environments that result in the loss of top talent. On the other end of the pendulum, being overly compassionate leaves a vacuum around attention to results. Compassionate Accountability reveals the truth behind, and provides an actionable framework for, six common myths surrounding compassion: Compassion is empathy in action; Compassion is about alleviating suffering; Compassion is soft; Compassion is for selfless servant leaders; Some people just have it; Compassion and accountability are opposites. Finding harmony between compassion and accountability leads to improved results and a thriving culture because the fact is, true compassion can't exist without accountability
Includes bibliographical references and index.
Keywords: Compassion